2011
DOI: 10.1080/00071668.2011.581269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caponisation on lipid and fatty acid composition of intramuscular and abdominal fat of medium-growth broilers

Abstract: 1. Capons and intact male broilers were used to investigate the effects of caponisation on intramuscular fat and abdominal adipose tissue lipid content and fatty acid profile. 2. Capons had significantly higher total lipid content (P<0·05). 3. Neutral lipids were the major fractions in intramuscular and abdominal fat but their proportions differed significantly among groups and tissues (P<0·05). 4. The predominant saturated, monounsaturated and polyunsaturated fatty acids in all samples were C16:0, C16:1 ω-9, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 33 publications
4
10
0
1
Order By: Relevance
“…In contrast, our results show an increase in 20:4n6 values in abdominal fat similar to the results obtained by Sinanoglou et al. (). Our results find no significant influence of castration on 20:4n6 in breast muscle and liver tissue, which is in agreement with the results obtained by Miguel et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, our results show an increase in 20:4n6 values in abdominal fat similar to the results obtained by Sinanoglou et al. (). Our results find no significant influence of castration on 20:4n6 in breast muscle and liver tissue, which is in agreement with the results obtained by Miguel et al.…”
Section: Discussionsupporting
confidence: 93%
“…() and Rikimaru et al. () did not find significant differences; meanwhile, other authors found an increase in SFA content in thigh muscle (Sirri et al., ; Masek et al., ) or an increase in intramuscular fat, and a decrease in abdominal fat (Sinanoglou et al., ). The most important variable in castrated male animals is the lack of testosterone, which may directly influence lipid metabolism.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, the surgery resulted to reducing the content of stearic acid (C18:0) by 35.1 % and that of arachidic acid (C20:0) by 54.3 % in the thigh muscle (Table 6). A significantly higher percentage of saturated fatty acids in castrated chickens was also observed by Sinanoglou et al (2011). Other authors did not find any significant differences in the saturated/unsaturated fatty acids ratio (Sirri et al 2009) or observed a lower percentage of fatty acids in castrated birds (Tor et al 2005).…”
Section: Resultsmentioning
confidence: 76%
“…The level of testosterone is negatively correlated with adiposity (Chen et al, 2006). The increase in the amount of fat tissue and intramuscular fat, which is dependent on the capons' breed and age at slaughter, improves the flavour values of meat (Chen et al, 2006;Sinanoglou et al, 2011;Volk et al, 2011). This is important to consumers, who seek products that are more attractive than the common poultry foods.…”
Section: Discussionmentioning
confidence: 99%